Auction characteristics, seller reputation, and closing prices: evidence from eBay sales of the iPhone. (10th March 2010) - Depken II, Craig A.; Gregorius, Brandon
We analyse auctions from eBay to determine whether seller reputation, auction timing, and auction aesthetics influence closing prices. Using a large sample of Apple iPhone auctions, we find that closing prices are influenced by the level of seller reputation, and sellers with no reputation at stake suffer a substantial loss in closing prices. Moreover, during the sample period investigated there were small arbitrage opportunities in deciding when the auction would end, and in certain aesthetics of the auction, such as using bold fonts and including pictures of the product for sale. These arbitrage opportunities were somewhat reduced when e-bay increased the prices it charged for these aesthetic upgrades six months after the sample period investigated.